Weakness in the international legal system: the case of Ukraine - Polkovanova, Sofya (Riga Graduate School of Law, 2019)
The purpose of this thesis is to evaluate the international legal system and determine whether it is able to deal with powerful states on equal footing. In order to achieve this purpose, it is necessary to go back to the origins of international law. First, consider international law principles and see how and to what extent the core notion of the international law theory is applied to the contemporary world. Second, it is important to provide support for the assumptions and findings made by existing case law, in the case in question, the annexation of Crimea into the Russian Federation in 2014.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Ukraine